O. Shumenko, V. Nazarchuk. The main features of translation of comparative phraseological units in german discourse. - O. Shumenko; V. Nazarchuk (Philological Treatises, 2020)
The article deals with the peculiarities of the use of translation transformations in the translation of comparative phraseological units, in the reproduction of the German novel E.M. Remark in Ukrainian. The authors analyze the different methods of using translation transformations in the translation of comparative phraseological units from German to Ukrainian.